Changes in histopathological features of adolescent rat livers due to subchronic exposure to Chlorpyrifos, Carbofuran, and Cypermethrin - Muhammad Ihwan Narwanto; Siti Jamalia; Yuli Hermansyah (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2023)
Insecticides are the most widely used type of pesticide in various fields, such as agriculture, plantation, industry, and household activities. Only 1% of the insecticides used work effectively to attack the target and the remaining 99% are released freely into water, soil, and air and finally have an impact on non-target organisms. Chlorpyrifos, carbofuran, and cypermethrin were the most widely used insecticides in their respective groups, namely, organophosphates, carbamates, and pyrethroids. This study aims to determine the changes in histopathological features of adolescent rat livers due to subchronic exposure to chlorpyrifos, carbofuran, and cypermethrin. Adolescent livers have a faster regeneration rate but are more susceptible to damage than the older age group. This study used 30 male Wistar rats which were divided into 5 groups, namely, normal group (N), control group (K), chlorpyrifos group (P1), carbofuran group (P2), and cypermethrin group (P3). Subcutaneous injection of insecticide was carried out for 21 days. The scoring method used in the histopathological observations is Manja Roenigk score. Data analysis used the ANOVA test and continued with the LSD post hoc test. In this study, significant results were obtained, P<0.05, which indicated that there were significant differences in the histopathological features of the liver that were exposed to chlorpyrifos, carbofuran, and cypermethrin. The picture of liver damage was mostly found in the carbofuran group.